Planejamento familiar: um estudo sobre a experiência da Fundação Santa Casa de Misericórdia do Pará - SERRÃO, Ana Márcia Farias (Universidade Federal do Pará, 2017)
This dissertation entitled "FAMILY PLANNING: a study on experience in the hospital" aims to analyze the applicability of Law No. 9,263 / 96, which addresses the objectives of the National Family Planning Program. It also seeks to deepen knowledge on the subject of women and feminist movements in the context of reproductive rights and health policy. To facilitate the study, there was bibliographical and documentary research, interviews with women and men users of the searched service. The study's findings indicate that despite the legal advances in institutional practice there are many existing boundaries to enable a family planning that meets consistently the demands of feminist movements.